PROFIL LEUKOSIT TIKUS PUTIH YANG DIBERI AIR SEDUHAN KELOPAK BUNGA ROSELA MERAH (Hibiscus sabdariffa) - Pancawati Ariami; Hesti Suliastiningsih; Maruni Wiwin Diarti (Jurnal Kesehatan Prima, 2015)
Abstract: Roselle is a plant that has many benefits with vitamin C, iron ,folic acid , and amino acids  highly needed by the body. This study aimed to determine the effect of the provision of water steeping red roselle calyx (Hibiscus sabdariffa) on peripheral blood leukocyte counts in rats (Rattus norvegicus) Wistar strain. Pre Experimental Research done. The results showed the average number of leukocytes in peripheral blood of experimental animals before treatment was 4060 / µL, and after the treatment is 8120 / µL . This shows that red roselle calyx (Hibiscus sabdariffa) can increase the number of leukocytes of 4060 / µL . Based on the results of statistical tests Paired T - Test showed no significant difference steeping water provision red roselle calyx (Hibiscus sabdariffa) on peripheral blood leukocyte counts in rats (Rattus norvegicus) Wistar strain, the probability of 0.004 < α 0.05. Provision of water steeping red roselle calyx (Hibiscus sabdariffa) effect on the number of leukocytes in peripheral blood white rats (Rattus norvegicus) Wistar strain . The number of leukocytes increased 2 -fold with water provision steeping red roselle calyx after 9 days of treatment with a concentration of 2 % .